The American development model hidden agenda for the third world - Stauffer, Robert B. (1977)
The main thesis of this paper is that the American development model, instead of enhancing development, perpetuates underdevelopment and aggravates the dependency of Third World nations on industrially advanced societies. The obscurantist ideology of the model evades questions of human welfare (e.g., housing, malnutrition, health, education and mployment); hence the question "development for what?" arises. As a reaction, the article suggests that social scientists should (a) examine whether foreign "aid" helps develop self-reliance among people; (b) establish counter-paradigms to the American model by joining developmentalists - as those found in Latin America - who look critically outside the established academic models of development; and (c) work out a system of measurement employing social indicators to assess existing models along selected human well-being dimensions, and to detect exploitative relationships between industrialized nations and developing countries.
Keywords: Development administration; Public administration